2020
DOI: 10.3390/biomedicines8030043
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effects of GLP1 Analog and SGLT2 Inhibitor against Diabetic Cardiomyopathy in Type 2 Diabetic Rats: Possible Underlying Mechanisms

Abstract: The present study investigated the possible cardioprotective effects of GLP1 and SGLT2i against diabetic cardiomyopathy (DCM) in type 2 diabetic rats and the possible underlying mechanisms. Methods: Thirty-two male Sprague Dawley rats were randomly subdivided into 4 equal groups: (a) control group, (b) DM group, type 2 diabetic rats with saline daily for 4 weeks, (c) DM + GLP1, as DM group with GLP1 analogue (liraglutide) at a dose of 75 µg/kg for 4 weeks, and (d) DM + SGLT2i as DM group with SGLT2 inhibitor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Data from echocardiography revealed that DAPA administration improved the measurement of LV function (such as EF and FS) affected by I/R injury, and this was in line with a recent study revealing the positive effect of DAPA on the enhancement of LV function of Type II DM patients with stable heart failure [9]. Moreover, we showed that treatment of DAPA attenuated the rise in the levels of two AMI-associated enzymes (CK-MB and LDH) in response to I/R injury, which was in conformity with a study showing SGLT2 inhibitor exhibited cardioprotective effects and downregulated the serum CK-MB and LDH in DM rats [42]. Taken together, DAPA may have protective effect of cardiac function in the setting of AMI.…”
Section: Discussionsupporting
confidence: 92%
“…Data from echocardiography revealed that DAPA administration improved the measurement of LV function (such as EF and FS) affected by I/R injury, and this was in line with a recent study revealing the positive effect of DAPA on the enhancement of LV function of Type II DM patients with stable heart failure [9]. Moreover, we showed that treatment of DAPA attenuated the rise in the levels of two AMI-associated enzymes (CK-MB and LDH) in response to I/R injury, which was in conformity with a study showing SGLT2 inhibitor exhibited cardioprotective effects and downregulated the serum CK-MB and LDH in DM rats [42]. Taken together, DAPA may have protective effect of cardiac function in the setting of AMI.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated that SGLT2Is lessened cardiac macrophage infiltration and decreased inflammatory cytokines (TNFα and TGFβ) in diabetic mice. 93,96,105 Insulin resistance and hyperglycemia can activate a molecular marker, NLRP3, in DCM, leading to activation of procaspase 1, IL1β, and IL18. 106 A study proved that dapagliflozin attenuated NLRP3, ASC, IL1β, IL6, and caspase 1, as well as TNFα mRNA levels, markedly through the activation of AMPK in hearts of diabetic mice.…”
Section: Sglt2 Inhibitors and Inflammation Factors And Cardiac Fibrosmentioning
confidence: 99%
“…133 Dapagliflozin decreases tyrosinehydroxylase density and myocardial norepinephrine content, contributing to attenuation of myocardial damage and fibrosis, indicating that improved sympathetic nerve activity is a potential mechanism for the cardiac protection of SGLT2Is in DCM. 105 Chronic activation of the hexosamine biosynthetic pathway and subsequent excessive O-GlcNAcylation is associated with DM and affects heart function in hyperglycemia. O-GlcNAcylation impairs cardiac Ca 2+ homeostasis, mitochondrial function, and ERS by modulating key protein targets, such as phospholamban, calmodulin kinase II, and FOXO1, in the diabetic heart.…”
Section: Othersmentioning
confidence: 99%
“…• Decreased oxidative stress and cardiac myocyte apoptosis Hussein et al, 2020 Exenatide (24 nmol/kg once daily IP)…”
Section: Glp-1r Agonists and Diabetic Cardiomyopathy In Humansmentioning
confidence: 99%
“…The systolic and diastolic dysfunction were much more severe in the latter study, likely due to increased islet β-cell death and worsened T2DM with higher doses of STZ utilized (treatment for 5 days vs. 1 day). In male Sprague-Dawley rats subjected to T2DM via HFD supplementation for 8-weeks with STZ (35 mg/kg) administered at the 4-week time point, treatment with liraglutide (75 μg once daily) for the final 4-weeks increased both myocardial catalase activity and reduced glutathione levels, while decreasing caspase 3 expression (Hussein et al, 2020 ). This suggests that GLP-1R agonism attenuates T2DM-related increases in myocardial oxidative stress and cardiac myocyte apoptosis, respectively, key mediators of diabetic cardiomyopathy, though diastolic function was not assessed in this particular study.…”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 99%